Quantifying the nonclassicality of pure dephasing - Hong-Bin Chen (Nature Portfolio, 2019)
The presence of processes that cannot be simulated classically in open quantum system dynamics is acknowledged, but an exact quantifier for this non-classical character is still missing. Here, the authors provide a quantitative measure of non-classicality for purely dephasing evolutions.